2019
DOI: 10.31101/jhtam.1113
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depression: prevalence, outcomes and screening tools - a review of the literature

Abstract: Perinatal depression (PD) is a depressive disorder in women that occurs either during pregnancy and/ or within 12 months after delivery. PD has adverse outcomes not only for mothers, but also for their children and their family/husband. A review of literature was conducted to present a comprehensive review of the available research into depression, its prevalence, risk factors and the screening tools in the context of the perinatal period. The literature will provide the background for understanding perinatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Nursing babies in the NICU causes mothers to have high levels of stress that indirectly affects the success of breastfeeding (Alkozei, et al 2014).This is supported by other studies which found that the anxiety that the mother feels might have an impact on the process of breastfeeding the babies (Pratiwi & Glover, 2019).…”
Section: B Disruption In the Breastfeeding Processmentioning
confidence: 76%
“…Nursing babies in the NICU causes mothers to have high levels of stress that indirectly affects the success of breastfeeding (Alkozei, et al 2014).This is supported by other studies which found that the anxiety that the mother feels might have an impact on the process of breastfeeding the babies (Pratiwi & Glover, 2019).…”
Section: B Disruption In the Breastfeeding Processmentioning
confidence: 76%